2015
DOI: 10.9775/kvfd.2014.11934
|View full text |Cite
|
Sign up to set email alerts
|

İran’da Atların Viral Arteritisi Enfeksiyonunun Mevsimsel, Coğrafi, Yaş ve Cins Yayılımı

Abstract: The aim of this study was to estimate the prevalence of EVA in mare and stallion in various seasons, ages, breeds and regions of Iran. Totally, 470 blood samples which were taken from mares and stallions were tested for presence of EVA antigen and antibodies. Samples were collected in various seasons from various geographical parts of Iran. Blood and serum samples were taken from horses less than 1 year, 1-2 years, 2-3 years and more than 3 years old. Viral RNA and antibodies against EVA were detected in 4.46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Extraordinary prevalence of resistance against tetracycline, ampicillin, gentamicin, mezlocillin, enrofloxacin, and trimethoprim was also reported from USA (27), China (28), and Iran (29). Boost prevalence of resistance against routine types of antibiotic agents has been described previously (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Mashak (44) reported that prevalence of E. coli in raw meat, milk, and vegetables collected from Iran was 14%, 20%, and 31.25%, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Extraordinary prevalence of resistance against tetracycline, ampicillin, gentamicin, mezlocillin, enrofloxacin, and trimethoprim was also reported from USA (27), China (28), and Iran (29). Boost prevalence of resistance against routine types of antibiotic agents has been described previously (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Mashak (44) reported that prevalence of E. coli in raw meat, milk, and vegetables collected from Iran was 14%, 20%, and 31.25%, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…However, there is evidence that raw milk of animal species might contain different types of threatening foodborne pathogens. [2][3][4][5] Most cases of foodborne outbreaks are associated with the consumption of food contaminated with foodborne bacterial pathogens, [6][7][8][9][10][11][12][13][14][15][16] especially Staphylococcus aureus (S. aureus). [17][18][19][20] S. aureus is a bacterium of the Firmicutes family originating from the human nose and skin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, amplified samples were analyzed by electrophoresis (120 V/208 mA) in a 2.5% agarose gel stained with 0.1% ethidium bromide (0.4 μg/mL) [36]. Besides, UVI doc gel documentation systems (Grade GB004, Jencons PLC, London, UK) were used to analyze images [37][38][39].…”
Section: Pcr-based Detection Of Antibiotic Resistance Genesmentioning
confidence: 99%